Regional Economic Outlook, October 2019, Sub-Saharan Africa. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2019)
Growth in sub-Saharan Africa is expected to pick up, though at a slower pace than previously expected. This revision reflects a more challenging external environment, continued output disruptions in oil-exporting countries, and a weaker-than-anticipated growth in South Africa. The challenge for the region is to boost growth to create jobs for the growing labor force, while protecting against debt vulnerabilities and risks from a difficult global environment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet